A qualitative inquiry into cash waqf model as a source of financing for micro enterprises - Mohd Thas Thaker, Mohamed Asmy (Emerald Publishing Limited, 2018)
Purpose – This paper aims to explore the opinions and recommendations of various experts on the integrated cash waqf micro enterprise investment (ICWME-I) model, particularly in terms of its suitability, applicability and prospects in the market. Design/methodology/approach – The research involves primary data which are collected from semistructured interviews conducted with experts from various backgrounds. Thematic analysis was used to examine the data. Findings – The experts support the suitability of the ICWME-I model in providing financial services to micro enterprises. They highlight the importance of establishing, managing and operating ICWME-I model under the aegis of the State Islamic Religious Council in Malaysia or the corporate sector. They further emphasize that the characteristics of micro enterprises, the element of sustainable funding, the importance of proper management and administration, legal matters and public awareness are key factors that influence the sustainability of the ICWME-I model. Originality/value – This paper adds to the literature on waqf and micro enterprises especially from the Malaysian context. The paper validates the ICWME-I model in terms of its suitability, applicability and prospects in the market by interviewing experts fromvarious backgrounds.